Цитадель: роман / Вячеслав Грацкий - Грацкий Вячеслав Вениаминович (Магия фэнтези, 2007)
Экземпляры: Ф. 4 (20191105) / Инвентарный номер: 47315 / Цена: 50.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Г 67 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44